The assessment of dentofacial esthetics in restorative dentistry: a review of the literature - Frese, Cornelia; Staehle, Hans Jörg; Wolff, Diana (The journal of the American Dental Association, 2012)
Background: The authors conducted a literature review to determine how dentofacial esthetics can be evaluated in restorative dentistry and which quantifiable clinical parameters can be used for this assessment of dentofacial esthetics. Types of Studies Reviewed: The authors selected 35 studies that focused on assessment strategies for dental professionals. The primary inclusion criteria were intraoral and extraoral esthetic assessment methods and indexes or rating scales evaluating esthetics in restorative dentistry. Results: The studies' protocols and assessment methods were heterogeneous. The authors grouped the studies into six categories according to topic: golden proportion, soft-tissue measurement, smile and smile line assessment, orofacial indexes and scales, incisor proportion and angulation, and facial esthetics. These categories included various esthetic parameters, including the smile line, lip line, incisal offset, location of dental and facial midline, incisor angulations and width to height ratios of the maxillary anterior teeth, gingival contour, and root coverage and papilla height. These parameters should be considered when providing dental treatment in the anterior area, as they allow for quantification and objective judgment. Clinical Implications: The findings of this review might increase interest in a comprehensive dental esthetic index that allows for objective quantification and intrastudy and interstudy comparison of dental treatment outcomes.